Synthesis of Some novel Azomethine Oxide Derived from Aromatic Oximes and their Anti-microbial Studies - Mohammed, Jihad H.; Qaddo, Akram N. M.; Muhammad Salih, Nabaz A.; Omar, Faeza B. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
The organic compound category known as azomethine oxides has garnered significant attention due to its potential for bioactive and pharmacological effects, as well as its role in organic syntheses. Existing literature offers various methods for producing derivatives of these compounds. This study, in particular, concentrates on the creation of several aromatic oximes through the reduction of corresponding aldehydes. Furthermore, these oximes are employed in the generation of new azomethine oxides through a condensation reaction with selected aldehydes. The molecular structure of the synthesized azomethine oxides is determined using techniques such as Fourier-transform infrared spectroscopy, 1H-NMR, and 13C-NMR. Finally, the antimicrobial effectiveness of these compounds was assessed against Escherichia coli (gram-negative bacteria), Staphylococcus aureus (gram-positive bacteria), and Candida albicans (fungus). The synthesized compounds were obtained with high purity and yielded excellent results. Furthermore, the data demonstrates that these azomethine oxides exhibit significant antimicrobial activity when compared to standard drugs.